Aprendizagem da arte e formação de educadores - Siqueira, Juliano Reis (2009)
The research line in Arts Education and the Research Program of Graduate Studies on Education in the Federal University of Santa Maria aims at thinking about learning the art and its importance in the education of teachers. Through interviews with teachers interested in the education of teachers and artists the strategies, ways and conditions to learn art are analyzed. Corrêa based on his understanding of school educational limits presents his experience of the willing learning in workshops. Kastrup states that art learning becoming a problematic field, as the teacher is one who works together, share experiences of a field problem, shows the reverse of the representation acting outside the field, working to overcome such a problematic field. Goulart based on his teaching activities highlights the teacher s non-authoritative role in the teachers education. Peciar remarks the testing of the intuition, the question of rules and models and emphasizes, in a pedagogy of art, the abandon of the teacher s critics in favor of the reception of students production. From the contributions presented it can be emphasized the importance of an education mixed with the production of difference, affected by the meetings (of people, situations and perspectives) and fostering of multiple ways of learning.